PERAN MEDIA VIDEO DALAM MENINGKATKAN PEMAHAMAN SISWA PADA POLA IRAMA MATA PEMBELAJARAN SENI BUDAYA DI MIM KETRO 1 - Mustaqim, Tri Rohman; Imtihana, Ezif Rizqi (INSTRUKTUR INSTRUKTUR: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to explore the role of video media in enhancing third-grade students’ understanding of rhythm patterns in the Cultural Arts subject at MI Muhammadiyah Ketro 1. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results indicate that video media has a significant impact on improving students' comprehension. The visualization of rhythm patterns through video helps students easily identify and differentiate between beats and tempos, which were previously difficult to grasp through verbal explanation alone. Additionally, video media increases students’ engagement and enthusiasm during the learning process. Students became more active in discussions, more confident in practice, and demonstrated creativity in creating their own rhythm patterns. However, the study also identified several challenges, such as limited access to devices and unstable internet connectivity. Despite these obstacles, the use of video media proved to be an effective learning strategy that supports the improvement of students' conceptual understanding and musical skills in rhythm pattern lessons within cultural arts education